Wacana Postmodern dalam Seni Rupa Kontemporer Indonesia - I Gede Arya Sucitra (Journal of Contemporary Indonesian Art, 2015)
The Postmodern Paradigm in Contemporary Indonesian Art. This article is a theoretical production of the postmodern concept underlying conception of the birth of contemporary art. Reinforced by the growing tendency of young artists in Indonesia who cultivate the visual power of traditional culture combined with the latest aesthetic tendency. As a result, the works produced into works that are global, but still showing traces of the value of tradition. Theoretical studies on more articles will be initiated through the method of literature review. The study will be conducted for the analysis of the aesthetic concept of contemporary art through the study of literature from a wide variety of art books, writing art thinkers, and creators of art. The exposure of definitions and statements of art in this article aims to map out the direction of thinking contemporary art world in general and in particular examine the realm of creation of works of contemporary art in Indonesia.Keywords: postmodern, contemporary art, traditional culture